Effect of circumferential resection margin status on survival and recurrence in esophageal squamous cell carcinoma with neoadjuvant chemoradiotherapy - Gu, Yi-Min; Yang, Yu-Shang; Kong, Wei-Li; Shang, Qi-Xin; Zhang, Han-Lu; Wang, Wen-Ping; Yuan, Yong; Che, Guo-Wei; Chen, Long-Qi (Frontiers in Oncology, 2022)
Background: The aim of this study was to investigate whether circumferential resection margin (CRM) status has an impact on survival and recurrence in esophageal squamous cell carcinoma after neoadjuvant chemoradiotherapy. Methods: We screened patients with esophageal squamous cell carcinoma who underwent esophagectomy from January 2017 to December 2019. The CRM was reassessed. Patients were grouped into a CRM of 1 mm or less (0 < CRM ≤ 1 mm) and a CRM greater than 1 mm (CRM>1 mm). The impact of CRM on survival was investigated using Kaplan–Meier analysis and Cox regression modeling. The optimal CRM cut point was evaluated using restricted cubic spline curve. Results: A total of 89 patients were enrolled in this study. The CRM status was an independent risk factor for the prognosis (HR: 0.35, 95% CI: 0.16-0.73). Compared with a CRM of 1 mm or less, a CRM greater than 1 mm had better overall survival (HR: 0.35, 95% CI: 0.16-0.73, log-rank P = 0.011), longer disease-free survival (HR: 0.51, 95% CI: 0.27-0.95, log-rank P = 0.040), and less recurrence (HR: 0.44, 95% CI: 0.23-0.85, log–rank P = 0.015). We visualized the association between CRM and the hazard ratio of survival and identified the optimal cut point at 1 mm. Conclusions: A CRM greater than 1 mm had better survival and less recurrence compared to a CRM of 1 mm or less. A more radical resection with adequate CRM could benefit survival in patients with esophageal squamous cell carcinoma after neoadjuvant therapy.